Criopreservação do sêmen de macaco-prego (Sapajus apella Linnaeus, 1758): avaliação de diferentes diluidores, concentração de glicerol e antioxidante catalase - LEÃO, Danuza Leite (Universidade Federal do Pará, 2017)
The main objective of the present study was to establish an efficient semen cryopreservation protocol in Sapajus apella for maintaining sperm viability. For this, we compared the performance of TES-TRIS, CWS and ACP-118® extenders during the seminal coagulum dissolution and cooling. Then, in order to improve the sperm parameters, we also determined the glycerol concentration (3; 5 and 7%) as well as to evaluate the effect of catalase antioxidant (10 µg and 50 µg). Therefore, six adult males of S. apella from the National Primate Center were used. Semen was collected by electro-ejaculation with rectal probe after chemical restraint of animals with ketamine and xylazine hydrochloride. In the first phase of the project, the semen obtained was diluted in TES- TRIS, CWS and ACP®-118 extenders, kept in a water bath at 37 °C. After coagulum dissolution, the semen was cooled in the refrigerator at 4 °C for 90 minutes and evaluated after 28h for motility, vigor and plasma membrane integrity percentage before and after the cooling. ACP®-118 was the best extender to preserve the motility sperm and plasma membrane integrity after 28 hours of incubation. Based on these results, cryopreservation was performed by evaluation of different concentrations of glycerol (3, 5, and 7%). The cryopreserved sperm to 3% glycerol had better results. In the second project phase was performed S. apella semen cryopreservation in ACP®-118 extender supplemented or not with catalase antioxidant (10 µg/mL and 50 µg /mL). All treatments were effective in maintaining sperm parameters and was possible to recovery the post-thaw motility. The catalase 50 treatment was the best for maintenance of the vigor after cooling and plasma membrane integrity in post-thaw sperm. So, we concluded that ACP-118® extender can be efficiently used for S. apella semen cryopreservation added 3% glycerol, moreover, the addition of the catalase antioxidant showed beneficial effect during this process.